Modification of Da'wa through Internalization of Da'watainment in Prank Video Content on Youtube - Mazaya, Vyki; Novitasari, Rizza Olivia (Proceedings of International Conference on Da'wa and Communication, 2021)
Da'wa efforts in the era of disruption with the presence of online-based new media provide a space of expression for anyone to convey da'wa through unlimited creativity with various innovations. Da'wa is not always delivered seriously in a formal atmosphere but da'wa can be packaged in a relaxed manner, can be enjoyed in a relaxed and even entertaining way. Collaboration between da'wa and entertainment known as da'watainment is expected to be able to attract the millennial generation who are the largest users of Youtube media so that da'wa messages can be packaged through communication media that are close to the world of the millennial generation with concepts that are trending among millennials, one of which is prank. Prank content had gone viral after drawing a lot of criticism and protests because it contained useless substances and actually caused harm. Creative ideas are needed to modify useless content into useful content that is still interesting and entertaining. This study describes qualitatively descriptive from the data obtained from virtual observations on prank content and prank shalawat on Gus Aldi's Youtube channel which inspires millennial da'i-da'i in conveying da'wa messages through Youtube. In this content there is a varied structure in broadcasting shalawat as well as other messages of Islamic teachings which are also conveyed in a humorous, relaxed, and entertaining way.